The influence of contradictions in existing specifications and technical documentation on decision-making at design of compressor stations of objects of oil and gas industry - A. D. Vanyashov; A. V. Zherelevich; E. M. Vasenko (Омский научный вестник: Серия "Авиационно-ракетное и энергетическое машиностроение")
The problem situations arising when design gas compressor stations of high pressure for the oil and gas industry are considered. Now we face the contradictory requirements of the existing specifications and technical documentation taking place and also lack of necessary requirements and calculation procedures. In work the solutions concerning the use of safety valves on pressure lines of the compressor, the rational choice and arrangement of shutoff valves and back pressure valves, the choice of diameters of technological pipelines, calculation of «equilibrium» pressure at an emergency stop of compressor installation are proposed. Based on the carried-out analysis of possible circuit and arrangement decisions, taking into account the greatest possible satisfaction to requirements of the operating specifications and technical documentation, introduction to estimated practice of the new offered techniques, the choice of an ancillary technology equipment and configuration of compressor station is done. The designed object meets requirements of technological effectiveness, working capacity on varying duties, safety of maintenance in the conditions of high pressures and temperatures of gas